Nutraceutical Potential of Havardia pallens and Vachellia rigidula in the Diet Formulation for Male Goat - Jesús Humberto Reyna-Fuentes; Cecilia Carmela Zapata-Campos; Jorge Ariel Torres-Castillo; Daniel López-Aguirre; Juan Antonio Núñez-Colima; Luis Eliezer Cruz-Bacab; Fabián Eliseo Olazarán-Santibáñez; Fernando Sánchez-Dávila; Aida Isabel Leal-Robles; Juan Antonio Granados-Montelongo (Metabolites, 2025)
Background: Xerophilous scrubland is a semi-desert ecosystem characterized by a wide diversity of shrubs, which have secondary compounds with nutraceutical potential that could be used as feed for livestock, specifically by goats, since this species has developed behavioral and physiological adaptations that allow it to take advantage of the plant resources of said scrubland. Objective: To evaluate the nutraceutical potential of Havardia pallens and Vachellia rigidula, native species of the xerophilous scrubland, when incorporated as ingredients in goat diets. Methods: Integral diets for male goats were prepared, formulated with 35% inclusion of Havardia pallens, Vachellia rigidula, and Medicago sativa, the latter used as a plant control species. The content of flavonoids and total phenols was compared using colorimetric methods, and the antioxidant capacity was measured using the FRAP method. RP-HPLC-ESI-MS characterized the bioactive compounds in the different extracts. Statistical analysis was performed by ANOVA. Results: The aqueous extraction of Vachellia rigidula showed the highest concentration of total phenols (<semantics><mover accent="true">x¯</mover></semantics> = 18.22 mg GAE/g−1), followed by the ethanolic extract in the same species (<semantics><mover accent="true">x¯</mover></semantics> = 17.045 mg GAE/g−1). Similarly, Vachellia rigidula presented the highest antioxidant capacity (<semantics><mover accent="true">x¯</mover></semantics> = 144,711.53 µmol TE/g−1), while Medicago sativa presented the lowest (<semantics><mover accent="true">x¯</mover></semantics> = 11,701.92 µmol TE/g). The RP-HPLC-ESI-MS analysis revealed that Vachellia rigidula presented a higher abundance of flavones, catechins, flavonols, methoxyflavones, and tyrosols. However, Harvardia pallens presented higher levels of methoxycinnamic and hydroxycinnamic acids. One-way ANOVA results showed that diets containing 35% Vachellia rigidula and Havardia pallens significantly contrasted (p < 0.05), increased the content of secondary compounds and antioxidant capacity compared to the control species. Furthermore, including Vachellia rigidula led to a significantly higher antioxidant capacity (p < 0.05) than diets with Havardia pallens or Medicago sativa. Conclusions: Incorporating the leguminous shrubs Vachellia rigidula and Havardia pallens into the formulation of comprehensive diets for buck goats improves the content and availability of phenols, flavonoids, and antioxidants. However, in vivo evaluation of these diets is important to determine their physiological and productive effects on the animals.